Protocol of a collaborative evaluation systematized non-systematic reviews by “DESCreview”, a Design tool for Evaluating risk of bias/quality in Systematized and sCoping reviews - Alexis Descatha; Aurélie Mayet; Grace Sembajwe; Marc Fadel (Archives of Public Health)
Abstract Background . Reproducible reviews that have a systematized approach, such as scoping, mapping, rapid, and other non-systematic reviews (henceforth, referred to as Scoping et al. reviews), have become a necessary step in a wide range of observational studies for public health research. Nevertheless, the quality of such Scoping et al. reviews is never questioned or evaluated. We propose a general-purpose tool for assessing the quality and risk of bias of Scoping et al. reviews, using a collaborative evaluation. Methods This Scoping et al. reviews tool (DESCreview, Design tool for Evaluating risk of bias/quality in Systematized and sCoping reviews) consists of a nine-domain assessment with four possible probabilities of quality. It includes the following domains in three parts: (A) Items applicable to all Scoping et al. reviews (Selection of papers; Classification; Extraction; Conflict of interest; Specific domain relevant to the question); (B) Items applicable to some Scoping et al. reviews (Preregistration and protocol difference, Risk of bias); and (C) Items only applicable for systematic reviews (Meta-analysis (if applicable), Strength of evidence). Each of the nine domains is rated from “Very high quality with low risk of bias” to “Very low quality with high risk of bias”. The overall confidence is assigned by combining all the nine domains into an overall strength rated: high, moderate, low, critically low. These four categories would be included in the review as the “calibration”. We also propose a collaborative evaluation, involving all potentially interested colleagues, using an online questionnaire. In the absence of a reference method, the validation study will be based on a comparison with AMSTAR-2, and feedback from user experience resulting in the production of a paper after one year of testing. Discussion DESCreview allow simple general-purpose tool for assessing the quality and risk of bias of systematized review in occupational and public health. The originality also lies in the collaborative validation process.